2006
DOI: 10.1590/s0103-64402006000400007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of commercially available and experimental potassium oxalate-based dentin desensitizing agents in dentin permeability: influence of time and filtration system

Abstract: This study evaluated the influence of time after application of oxalate solutions in reducing dentin hydraulic conductance. Fifty dentin discs were obtained from extracted human third molars and assigned to 5 groups (n=10), according to the desensitizing agent used: Group I: OxaGel; Group II: experimental agent DD-1: Group III: experimental agent DD-2. In Groups IV and V, a placebo gel and deionized water were used as control, respectively. The agents were applied for 3 min, washed out and the hydraulic conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 17 publications
1
47
0
6
Order By: Relevance
“…Greenhill and Pashley (17) reported that 30% potassium oxalate reduced dentin permeability by 98% in vitro. Another study (12) found that various potassium oxalate formulations decreased dentin permeability by approximately 75%, indicating the effectiveness of these products. Laboratory tests of desensitizing agents are conducted to evaluate their effectiveness or to predict their clinical performance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Greenhill and Pashley (17) reported that 30% potassium oxalate reduced dentin permeability by 98% in vitro. Another study (12) found that various potassium oxalate formulations decreased dentin permeability by approximately 75%, indicating the effectiveness of these products. Laboratory tests of desensitizing agents are conducted to evaluate their effectiveness or to predict their clinical performance.…”
Section: Discussionmentioning
confidence: 95%
“…This mechanism explains why desensitizing agents usually act in short-and longterm bases (11,12). Calcium chloride and potassium phosphate solutions have been tested in vitro (13,14) and in vivo (15), and may work similarly.…”
Section: Introductionmentioning
confidence: 99%
“…Para os estudos de condutividade hidráulica, dois métodos de preparação de espécimes são possíveis. Um deles preconiza o uso de discos de dentina (KOLKER et al, 2002;PEREIRA;SEGALA;GILLAM, 2005;PEREIRA;MARTINELI, 2006;KOMABAYASHI et al, 2010) e o outro utiliza segmentos de coroas (DE ANDRADE E SILVA et al, 2007;DE ANDRADE E SILVA et al, 2009;RUSIN et al, 2010). Pashley (1986) afirma que os discos de dentina são mais utilizados nesses estudos devido à facilidade de manuseio e um bom acabamento dos espécimes, uniformidade de espessura, além de possibilitarem a delimitação da área de superfície a ser testada através do uso de uma câmara de filtração.…”
Section: Da Metodologiaunclassified
“…Como o dispositivo apresenta seus componentes interligados, o deslocamento linear realizado pela microbolha é convertido em deslocamento de volume através do disco de dentina, em função do tempo (KOLKER et al, 2002;PEREIRA;SEGALA;GILLAM, 2005;PEREIRA;MARTINELI, 2006).…”
Section: Da Metodologiaunclassified
See 1 more Smart Citation